Specification for pressboard and presspaper for electrical purposes. Specifications for individual materials. Requirements for presspaper, types P.2.1, P.4.1, P.4.2, P.4.3, P.6.1 and P.7.1 Part 3-2, (15th January 1995) - British Standards Institution,
No abstract available